LITERASI BUDAYA DAN KEWARGAAN PADA ERA REVOLUSI INDUSTRI 4.0 SEBAGAI UPAYA DALAM MEMPERKUAT MODERASI BERAGAMA DI INDONESIA - Mahmudi Hanafiah; Nasrullah Nasrullah (Tatar Pasundan : Jurnal Diklat Keagamaan, 2022)
This article aims to provide answers about the role of literacy and citizenship in the industrial revolution 4.0 era to strengthen religious moderation in Indonesia. This research is qualitative with a descriptive nature and normative-sociological approach. Library research by using content analysis method is also applied. The results conclude that religious diversity in Indonesia must be combined to create a beauty. In combining these differences, precise steps are required. Cultural literacy and citizenship in the industrial revolution 4.0 era are steppingstones towards a surefire step which is the main concept, religious moderation. Islam commands to apply an attitude of religious moderation with the principles of justice, balance and tolerance with established boundaries. By applying religious moderation’s attitude born from cultural literacy and citizenship, unity between Indonesian citizens will be embedded, for their national identity. Keywords: literacy; religious moderation; Industrial Revolution 4.0